Faecal microbiota transplantation for Clostridium difficile infection in the United Kingdom. (June 2015) - Porter, R.J.; Fogg, C.
Abstract: Faecal microbiota transplantation (FMT) has been shown to be highly effective in treating recurrent Clostridium difficile infection, but to date there have been no data from the United Kingdom. An electronic survey was developed at Portsmouth Hospitals' National Health Service (NHS) Trust and sent out to UK hospital specialists utilizing the contact databases of the British Infection Association and the Royal College of Gastroenterologists. A total of 162 responses were received, representing nearly one in every seven of the United Kingdom's infection specialists and a response from one in every two UK NHS acute trusts or boards. Ninety-six per cent believe that the evidence base supports the use of FMT, and 94% reported consulting on at least one patient a year in whom they would recommend FMT. However, only 22% reported FMT use in their institution in the last 10 years, and 6% reported performing more than ten FMTs in the last 10 years. Concerns with patient acceptance, donor selection, availability of screened faecal solution, feasibility of procedure and availability of local expertise were reported as inhibiting the use of FMT. More than 90% of respondents would like access to regional guidelines, prescreened faecal solution and expert advice to facilitate implementation, and more than two thirds of respondents would support a regional FMT referral centre. A large gap exists in the United Kingdom between physicians desire to use FMT and the ability and facilities to provide it as a therapy at the bedside.